Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) - Hsun-Yu Lan; Farok Afero; Cheng-Ting Huang; Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou (Fishes, 2022)
Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study conducted an economic analysis of the expansion of large submersible cage culture by selecting two premium species of snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) and examined the profitability of large submersible cage culture investment. This study found that the current operation of four-unit cages highlighted a negative net present value and internal rate of return with a payback period of over ten and six years, respectively. Large submersible cage culture can be financially profitable when its operation unit expands from 8 to 24 units. Increasing unit cages to eight incurred a gross margin of 17.09%, BCR 1.21, with a payback period of 5.36 years. Expanding the operation to 24-unit cages was a potentially lucrative investment with a gross margin of 18.51%, BCR 1.23, PI 2.15, internal rate of return of 20.84%, and a payback period of 3.55 years. Sensitivity analyses revealed that market price and survival rate significantly impact the profitability of large submersible cage culture. Finally, it is suggested that producers could invest in 8-unit cages and maintaining the survival rate of snubnose pompano and cobia at 80% and 40%, respectively.